Analysis of agile supply chain enablers for an Indian manufacturing organisation - Patel B.S.; Tiwari A.K.; Kumar M.; Samuel C.; Sutar G. (My University, 2025)
The objective of present work is to categorise agile supply chain (ASC) enablers and examine its relative importance for better implementation of agility in perspective of the Indian manufacturing industry. This study deploys, analytic hierarchy process (AHP), a popular multi-criteria decision making (MCDM) tool as a solution methodology, such that the decision problem breaks into a hierarchy of different levels constituting goal, criteria and alternatives. The results show that there are three enablers namely virtual enterprises, customer satisfaction and adaptability are among the top priority enablers; enabler collaborative relationship is the moderate priority enabler and remaining three enablers i.e., use of information technology, market sensitivity and flexibility are the lowest priority enablers. To effectively implement agility in the supply chain, this study proposes that the manufacturing industries need to focus on the most important ASC enablers and also address the enablers with the least important at a later stage. Copyright © 2020 Inderscience Enterprises Ltd.